MBTI Personality Patterns among University Lecturers - Rashid, Sinai Hamid; Manukh, Sabah Marshood (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the (personality patterns) prevailing among university lecturers, and the statistically significant differences according to the variable (specialization, gender). The current research sample consisted of (320) male and female lecturers, who were selected randomly from Tikrit University lecturers, of both sexes and scientific and human specializations. The personality patterns test (MBTI) was applied, and after completing the psychometric properties of the scale, from validity, reliability and discrimination, the final scale consisted of 50 paragraphs in the final form and was applied to the research sample. Using the following statistical methods, T-test for one sample and two independent samples - Pearson correlation coefficient - Cronbach's alpha - Chi-square, showed the following results: 1- The dominant patterns that appeared in the study are the ESTJ pattern, which came as the most prevalent patterns, the ESTP pattern, the ENTP pattern, and the INTP patterns, while the rest of the patterns are less prevalent. 2- The patterns that are more prevalent among males are: They are the same as those prevalent among the research sample, while females were slightly less.